Disruptive democracy the clash between techno-populism and techno-democracy - Bloom, Peter (SAGE Publications, 2019)
Do new “smart” technologies such as AI, robotics, social media, and automation threaten to disrupt our society? Or does technological innovation hold the potential to transform our democracies and civic societies, creating ones that are more egalitarian and accountable?